Two sites for modulation of human sympathetic activity by arterial baroreceptors? - Kienbaum, Peter (Blackwell Science Inc, 2001)
1. Peroneal muscle sympathetic nerve activity (MSA), finger blood pressure and cardiac intervals were recorded at rest in 60 healthy subjects, aged 18–71 years. Arterial baroreflex control of MSA was analysed by relating each spontaneous sympathetic burst to the diastolic blood pressure and the cardiac interval of the heart beat during which the burst was generated. The results were expressed as blood pressure/cardiac interval threshold for occurrence of bursts, and as baroreflex sensitivity (i.e. the relationship between diastolic pressure/cardiac interval and burst strength). 2. Significant blood pressure/cardiac interval thresholds were present in all subjects and old subjects had less variability of thresholds than young subjects. In contrast, significant baroreflex sensitivity for diastolic pressure and cardiac interval was present in only 55 and 73 % of the subjects, respectively. There was no age-related difference in sensitivity. 3. In 40 subjects, two 5 min periods from the same recording were analysed. The number of sympathetic bursts and the threshold for occurrence of bursts were reproducible in all subjects. In contrast, significant baroreflex sensitivity in both periods was present in only 30 % (diastolic pressure) and 40 % (cardiac interval) of the subjects. 4. The results show that the baroreflex mechanisms regulating the occurrence and strength of sympathetic bursts are not identical. We suggest that the modulation occurs at two sites, one which determines whether or not a burst will occur, and another at which the strength of the discharge is determined.